Crystal structure of dimethyl (1α,2β,3α,4β,7β,8α,9β,10α) -13-isopropylidene-pentacyclo[8.2.1.14,7.02,9.0 3,8]tetradeca-5,11-diene-2,9-dicarboxylate, C21H 24O4 - Russell, R.A. (2014)
Zeitschrift fur Kristallographie - New Crystal Structures